First trimester prenatal diagnosis and detection of carriers of haemophilia A using the linked DNA probe DX13. Issue 6498 (21st September 1985) - Winter, R M; Harper, K; Goldman, E; Mibashan, R S; Warren, R C; Rodeck, C H; Penketh, R J; Ward, R H; Hardisty, R M; Pembrey, M E
Abstract : Although the use of a gene specific deoxyribonucleic acid (DNA) probe is the method of choice for detecting carriers of genes for rare genetic disorders, there will always be families in which such probes cannot be used because key subjects are not informative for restriction fragment length polymorphisms in or around the gene. In these cases closely linked DNA markers have to be used. An X chromosome specific DNA probe, DX13, which is closely linked to the haemophilia A locus on the X chromosome, was used for early prenatal diagnosis in two cases and to detect carriers in a series of nine possible heterozygote women. The first reported crossover between DX13 and the factor VIII:C locus was observed in this study. There are complexities inherent in using any linked DNA probe for assignment of genes, but such techniques are clinically important.